2017
DOI: 10.1111/bcpt.12721
|View full text |Cite
|
Sign up to set email alerts
|

Salivary DNA Methylation Profiling: Aspects to Consider for Biomarker Identification

Abstract: Is it not more comfortable to spit saliva in a tube than to be pricked with a needle to draw blood to analyse your health and disease risk? Many patients, study participants and (parents of) young children undoubtedly prefer non‐invasive and convenient procedures. Such procedures increase compliance rates especially for longitudinal prospective studies. Saliva is an attractive biofluid providing good quality DNA to study epigenetic mechanisms underlying disease across development. In this MiniReview, we will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 65 publications
(127 reference statements)
2
63
0
Order By: Relevance
“…These two tissues are also easily accessible and appear to reflect pathologic changes in the airways during asthma development. 26 In conclusion, we have shown that higher DNA methylation in the promoter-regulatory region of PM20D1 from infant saliva was associated with the occurrence of early childhood wheezing, especially in children of atopic mothers. Directionally consistent epigenetic alteration observed in cord blood of children with respiratory allergy suggests that this modification might operate from birth, while the confirmation in blood and nasal epithelia of school-aged children indicates possibly long-term changes.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These two tissues are also easily accessible and appear to reflect pathologic changes in the airways during asthma development. 26 In conclusion, we have shown that higher DNA methylation in the promoter-regulatory region of PM20D1 from infant saliva was associated with the occurrence of early childhood wheezing, especially in children of atopic mothers. Directionally consistent epigenetic alteration observed in cord blood of children with respiratory allergy suggests that this modification might operate from birth, while the confirmation in blood and nasal epithelia of school-aged children indicates possibly long-term changes.…”
Section: Discussionmentioning
confidence: 63%
“…While blood may be valuable for studying common immunologic processes, nasal and saliva epithelia, being probably closer to the methylation status of the bronchial mucosa than blood or cord blood DNA methylation, are likely better surrogate tissues for studies focused on local inflammation and environmental influences in asthma. These two tissues are also easily accessible and appear to reflect pathologic changes in the airways during asthma development …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many epigenetic modifications are often both tissue specific and transient [50]; as a result, quantification would require frequent tissue sampling, which in the case of muscle would be invasive and traumatic, and in the case of other tissue, such as the heart and brain, highly impractical [51]. However, early research suggests that salivary profiling of DNA methylation markers holds promise [52], making this approach potentially more attractive and practically realistic. Influence of genetics and epigenetics on traits associated with elite performance.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Sabine Langie, Belgium, received the Young Scientist Award and presented a lecture on Environmental and epigenetic programming of complex diseases. Interestingly, DNA methylation markers in saliva may turn out to be a useful early marker for children predisposed for respiratory allergy .…”
mentioning
confidence: 99%